2009
DOI: 10.1007/s10549-009-0371-8
|View full text |Cite
|
Sign up to set email alerts
|

Axillary web syndrome after axillary dissection in breast cancer: a prospective study

Abstract: International audienceThe axillary web syndrome is a self-limiting and frequently overlooked cause of significant morbidity in the early post-operative period after breast cancer axillary surgery, which is characterized by axillary pain that runs down the medial arm, limited shoulder range of motion affecting mainly shoulder abduction, and cords of subcutaneous tissue extending from axilla into the medial arm, made visible or palpable and painful by shoulder abduction. We evaluated the incidence of axillary we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
103
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 23 publications
10
103
2
Order By: Relevance
“…trigger point needling decreased the overall sensitivity in patients with fibromyalgia and decreased pain and increased range of motion in whiplash, post-mastectomy, and temporomandibular patients. 4,5,172,197 Patients with a hypersensitive trigger point in the upper trapezius muscle exhibited significantly enhanced somatosensory and limbic activity and decreased activity in the dorsal hippocampus compared with control subjects. 198 Using functional magnetic resonance imaging, Niddam et al showed that pain following the insertion of a needle into a trigger point combined with electrical stimulation is mediated through the periaqueductal gray in the brainstem.…”
mentioning
confidence: 98%
“…trigger point needling decreased the overall sensitivity in patients with fibromyalgia and decreased pain and increased range of motion in whiplash, post-mastectomy, and temporomandibular patients. 4,5,172,197 Patients with a hypersensitive trigger point in the upper trapezius muscle exhibited significantly enhanced somatosensory and limbic activity and decreased activity in the dorsal hippocampus compared with control subjects. 198 Using functional magnetic resonance imaging, Niddam et al showed that pain following the insertion of a needle into a trigger point combined with electrical stimulation is mediated through the periaqueductal gray in the brainstem.…”
mentioning
confidence: 98%
“…This condition is diagnosed clinically with physical exam revealing a web of palpable, cord like structures typically occurring several days to several weeks after surgery although it may present later [1][2]7,8]. In some cases the cords are not palpable, but the patient will endorse symptoms of pain and tightness while raising the arm [9].…”
Section: Discussionmentioning
confidence: 99%
“…(5,8,11,19,(23)(24)(25)(26) No standard of care has been established for the prevention or treatment of AWS. Manual therapies including myofascial release, scar massage, and lymphatic drainage techniques, as well as physical therapy, thermal therapy, surgery, and oral agents (anti-inflammatories and antibiotics (26) ) have been reviewed in detail by Yeung et al (8) Manual methods and physical therapy usually involve conservative treatment in several sessions over weeks or even months, with varying degrees of success in symptom reduction and cord resolution.…”
Section: Presentation (65 Weeks After Mastectomy)mentioning
confidence: 99%
“…Manual therapies including myofascial release, scar massage, and lymphatic drainage techniques, as well as physical therapy, thermal therapy, surgery, and oral agents (anti-inflammatories and antibiotics (26) ) have been reviewed in detail by Yeung et al (8) Manual methods and physical therapy usually involve conservative treatment in several sessions over weeks or even months, with varying degrees of success in symptom reduction and cord resolution. (8,15,(18)(19)(23)(24)(25)27) Manual axial distraction with firm digital pressure applied at various points to rupture the cord (usually at the first session) successfully relieved pain and movement limitations in a series of patients, (12) but, as with most prospective studies and case reports, any negative consequences for healing and particularly for risk of lymphedema were not investigated. (8) This retrospective case report describes the use of specific therapeutic massage techniques, including Swedish massage with passive ROM, to relieve signs and symptoms of AWS over two treatment sessions in a young woman who had recently undergone mastectomy and axillary surgery for breast cancer.…”
Section: Presentation (65 Weeks After Mastectomy)mentioning
confidence: 99%
See 1 more Smart Citation